Effects of Periodontal Treatment on Levels of Proinflammatory Cytokines in Patients with Chronic Periodontitis: A Meta-Analysis. (26th July 2022) - Ren, Jiahui; Li, Hong
Abstract : Background . During the progression of chronic periodontitis (CP), changes in the levels of inflammatory factors are detected in serum and gingival sulcus fluid (GCF). The aim of this meta-analysis was to systematically evaluate the effect of periodontal treatment on GCF and serum proinflammatory cytokines (IL-6, TNF- α, and IL-8) in patients with CP. Methods . Literature searches were performed through PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang Database. Randomized controlled trials comparing cytokine levels in periodontal treatment (experimental group) and control group between 2015 and 2020 were included. Results . There were a total of 13 studies included with 1220 patients. There were 630 cases in the experimental group and 590 cases in the control group. The meta-analysis showed that IL-6 levels in the GCF (SMD = − 2.88, 95% CI (-3.68, -2.09), P < 0.001 ) and serum (SMD = − 1.27, 95% CI (-1.72, -0.81), P < 0.001 ) were significantly lower in the experimental group compared with those before treatment. In addition, IL-8 levels in the GCF (SMD = − 2.08, 95% CI (-3.40, -0.76), P < 0.001 ) and serum (SMD = − 1.73, 95% CI (-2.76, -0.70), P < 0.001 ) were decreased after periodontal treatment, but more than that, a decrease was observed in TNF- α levels of GCF (SMD = − 3.98, 95% CI (-5.23, -2.73), P < 0.001 ) and serum (SMD = − 1.80, 95% CI (-3.16, -0.45), P < 0.001 ) after treatment. Conclusion . After periodontal therapy, the proinflammatory cytokines in the GCF and serum of patients with CP were significantly decreased compared with those before treatment, and the efficacy was remarkable.